PENGEMBANGAN INSTRUMEN ASESMEN DIGITAL DIGIRATIO ASSESS BERBASIS PROBLEM SOLVING MENGGUNAKAN WAYGROUND PADA MATERI RASIO DAN PROPORSI DI SMP - Dimas Rumahorbo; Lisda Karolin Br Barus; Erika Simangunsong; Derma Sarah Tia Wanka Purba; Eri Widyastuti (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
The mathematical problem-solving ability of junior high school students in the topic of ratio and proportion remains relatively low, particularly in understanding contextual problems and constructing solution strategies. Meanwhile, the assessments commonly used by teachers have predominantly taken the form of conventional tests that emphasize final answers over students' thinking processes. The advancement of digital technology has prompted a need for innovative assessment instruments capable of measuring problem-solving skills in a more interactive and authentic manner. This study aims to develop DigiRatio Assess as a problem solving-based digital assessment instrument using the Wayground platform on the topic of ratio and proportion at the junior high school level. This study employed a Research and Development (R&D) approach using the 4D development model, which consists of the define, design, develop, and Disseminate stages. The research subjects were 20 seventh-grade junior high school students and one mathematics teacher selected through purposive sampling. The developed instrument consists of 25 contextual items, comprising 20 multiple-choice questions and 5 fill-in-the-blank questions, arranged according to problem solving indicators. Validation results at the develop stage indicated that DigiRatio Assess received a very valid category from the content expert, assessment expert, and language expert, with an average percentage of 90.21%. At the Disseminate stage, student response results showed 41.5% in the strongly agree category and 56.5% in the agree category, while teacher responses reached 100% in the strongly agree category. The findings demonstrate that DigiRatio Assess is feasible for use as a practical, interactive, and effective digital assessment instrument to support the evaluation of students' mathematical problem-solving abilities on the topic of ratio and proportion at the junior high school level. ABSTRAK Kemampuan pemecahan masalah matematis siswa SMP pada materi rasio dan proporsi masih tergolong rendah, terutama dalam memahami masalah kontekstual dan menyusun strategi penyelesaian. Di sisi lain, asesmen yang digunakan guru selama ini masih dominan berbentuk tes konvensional yang lebih menekankan jawaban akhir dibandingkan proses berpikir siswa. Perkembangan teknologi digital mendorong perlunya inovasi instrumen asesmen yang mampu mengukur kemampuan pemecahan masalah secara lebih interaktif dan autentik. Penelitian ini bertujuan mengembangkan DigiRatio Assess sebagai instrumen asesmen digital berbasis problem solving menggunakan platform Wayground pada materi rasio dan proporsi di SMP. Penelitian ini menggunakan metode Research and Development (R&D) dengan model pengembangan 4D yang terdiri atas tahap define, design, develop, dan Disseminate. Subjek penelitian adalah 20 siswa kelas VII SMP dan satu guru matematika yang dipilih menggunakan teknik purposive sampling. Instrumen yang dikembangkan terdiri atas 25 soal berbasis konteks kehidupan sehari-hari, meliputi 20 soal pilihan ganda dan 5 soal isian, yang disusun berdasarkan indikator problem solving. Hasil validasi pada tahap develop menunjukkan bahwa DigiRatio Assess memperoleh kategori sangat valid dari ahli materi, ahli asesmen, dan ahli bahasa dengan rata-rata persentase sebesar 90,21%. Pada tahap Disseminate, hasil respon siswa menunjukkan 41,5% pada kategori sangat setuju dan 56,5% pada kategori setuju, sementara respon guru mencapai 100% pada kategori sangat setuju. Hasil penelitian menunjukkan bahwa DigiRatio Assess layak digunakan sebagai instrumen asesmen digital yang praktis, interaktif, dan efektif dalam mendukung evaluasi kemampuan pemecahan masalah matematis siswa pada materi rasio dan proporsi di SMP.